Agroforestry systems Production of "Quinta el Quiosco" (REICE: Revista Electrónica de Investigación en Ciencias Económicas, 2016)
This paper presents an analysis of the production system of production unit called "Quinta el Quiosco. The aim was to evaluate different aspects of the production system and the relationship between the system components and his economic contribution as well as to identify the role and integration of women as a generator of revenue and some alternative proposals by the producer before changes in climate. The methodology used was to apply a diagnosis of production systems by the technique of document analysis and field visits to the production unit. It has been found that the production unit and its production system is classified as an urban agroforestry system with some degree of internal consistency that generates enough income for the support of the family Lezama. The integration of women is evident in this system as a generator of income and livelihood of home. Climate variability presented in recent years ultimately led the producer to take alternative measures to address the environmental impact in their production.REICE Vol.3(6) 2015: 180-193
Keywords: Production System. Silvopastoral system. Women; Income; Climate variability